AKTIVITAS ANTIBAKTERI DARI DESAIN MIKROEMULSI MINYAK ATSIRI KAYU MANIS - Evelyn Djiuardi; Tutun Nugraha (Agroindustrial Technology, University of Trunojoyo Madura, 2017)
This research focused on the study of the capability of cinnamon essential oil as antibacterialagent, when it is made as a microemulsion solution. The study occupied further research onspecific type, concentration, and amount of emulsifier needed to make the cinnamon essentialoil miscible in water without causing destruction in its antibacterial activity. Four differentemulsifiers were tested, namely Tween 20, Tween 80, soya lechitin, and carboxymethyl cellulose(CMC) to stabilize the essential oil in water. The emulsifiers were used at 2% w/w, while theessential oil concentrations were varied at 0.5%, 1%, and 1.5%. In this study, the antibacterialactivity of the microemulsion solution of cinnamon essential oil was tested against two types ofpathogenic bacteria commonly found in foods, namely Staphylococcus aureus and Escherichiacoli. Among the four types of emulsifiers, which are used, CMC showed the best results as anemulsifier. The results of this study indicated that microemulsion solution has antibacterialactivity best is a combination between the CMC and the essential oil of cinnamon